Sustainable Agriculture in The Tobacco Industry: Future Trends and Challenges - Susanna Hartanto (Universitas Satya Terra Bhinneka, 2025)
Introduction/Main Objectives: Sustainable agricultural practices are crucial for tobacco production because they reduce environmental damage, support moral farming, and guarantee financial stability. Background Problems: In every stage of the tobacco life cycle from cultivation, production, distribution, consumption to post-consumption, tobacco poisons the environment and causes extensive harm. Novelty: Research about the tobacco industry's future trends and challenges in sustainability is still rare. Research Methods: The research looks at future trends and challenges in sustainable tobacco practices. The literature review was done in order to accomplish the research. Finding/Results: In order to overcome these obstacles and create a more sustainable model for tobacco production, it is imperative that innovative and sustainable farming methods be implemented, along with fair labor efforts and farmer support during the transition. Conclusion: A sustainable future for agriculture that benefits present and future generations requires striking a balance between economic interests and environmental, social, and cultural factors, as well as implementing regenerative agriculture.